Implementation Of Gender-Based Islamic Education In Madrasah; Analysis of Learning Equity Models, Strategies, and Barriers - Siagian, Zainidah (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
This study aims to analyze the models, strategies, obstacles, and efforts of gender-based learning equality at MTs Madinatul Ulum. MTs Madinatul Ulum has implemented several gender-based Islamic education models, including inclusive curriculum development by introducing influential female figures in Islamic history, such as Aisyah and Rabi'ah Al-Adawiyah. Non-discriminatory learning strategies are implemented to ensure equal participation between male and female students. In addition, educators are provided with training related to gender equality in an Islamic perspective, as well as anti-discrimination policies that provide equal opportunities for all students in terms of scholarships, awards and leadership. Parental involvement in supporting gender-based education is also an important factor. However, this implementation faces barriers such as educators' limited understanding of gender equality, the influence of traditional socio-cultural norms, a curriculum that has not fully integrated gender equality materials, and school policies that are not firm in prohibiting gender discrimination. To overcome these barriers, curriculum revision, clearer policies, and stronger support from parents and communities are needed. The research method used is case study-based qualitative to gain an in-depth understanding of the implementation of this gender-based education. This research is to contribute to the development of a more gender-equitable Islamic education at MTs Madinatul Ulum.